(untitled) (Baghdad Science Journal, 2024)
In the current research, a computer simulation program was designed and written according to the Monte Carlo method to serve as a virtual practical system instead of a real one. The program has been statistically, geometrically and numerically tested for virtual radioactive source-detector setup. The simulation program is carried out for NaI(Tl) detector, and once for Gieger-Muller counter, for a range of energy up to 10 MeV. The Law of Large Numbers and the Central Limit Theorem were used to test the accuracy and precision of the program’s workflow and an indication of how the results are close to their averages and, statistically, how they tend to a normal distribution. Generally, results of a number of detector efficiency types showed a high agreement with published experimental and several global codes results within a percentage error of 0.02-5% (i.e. the accuracy 95-99.98%) and the significance level reflects the precise of the algorithm of simulation. The accurate and precise estimation of the current simulation gives it the desired reliability. The current simulation program also showed flexibility and effectiveness in designing any nuclear source-detector system and providing the relevant workers or experimenters with indicators that help in the optimal design of a system in terms of equipment and geometrical configuration with the least time. It may take a few seconds to a few minutes of execution time for a personal computer with normal specifications. Unlike laboratory experiments which may take from several minutes to several hours. In addition, it provides an ideal work environment that is completely free of radiation hazards. Also, the current simulation provides a deep understanding of the interactions that occur in a real physical practical system.